Matanre Siri: Rekonstruksi Peningkatan Uniformitas Pernyataan Standar Akuntansi Keuangan No. 109 - Ismayanti Muksin; Saddan Husain (Jurnal Akuntansi dan Keuangan Islam, 2022)
The objective of this paper is to consider local culture as one of the factors that can help the National Amil Zakat Agency (BAZNAS) adhere more closely to the Statement of Financial Accounting Standards (PSAK) No.109, even though many Zakat Management Organizations (OPZ) have yet to do so. This paper employs an interpretive qualitative approach by contrasting the Indonesian Accounting Association's (IAI) Statement of Financial Accounting Standards with the Bugis Matanre Siri philosophy.In the context of the implementation of Statement of Financial Accounting Standards (PSAK No.109), Matanre Siri has developed into a philosophical value as well as a core value at the National Amil Zakat Agency (BAZNAS) of the Sidenreng Rappang Regency. Human resources with Makassar Bugis ancestry also play a significant role in bringing the implementation process and Bugis culture's Sulapa Eppa values together. At the National Amil Zakat Agency of Sidrap Regency, financial statements (financial statements) that are accountable and transparent are created by presentations based on the value of Matanre Siri, such as lempu' (honest). So that Metanre Siri is constructed with the intention of achieving uniformity or uniformity that has been established by the authorities.Tujuan dari penulisan ini adalah untuk mempertimbangkan budaya lokal sebagai salah satu faktor yang dapat membantu Badan Amil Zakat Nasional (BAZNAS) untuk lebih mematuhi Pernyataan Standar Akuntansi Keuangan (PSAK) No.109, meskipun banyak Organisasi Pengelola Zakat (OPZ) yang belum melakukannya. Makalah ini menggunakan pendekatan kualitatif interpretatif dengan membandingkan Pernyataan Standar Akuntansi Keuangan Ikatan Akuntan Indonesia (IAI) dengan filosofi Bugis Matanre Siri. Dalam konteks penerapan Pernyataan Standar Akuntansi Keuangan (PSAK) No.109), Matanre Siri telah berkembang menjadi nilai filosofis sekaligus nilai inti di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Sidenreng Rappang. Sumber daya manusia dengan keturunan Bugis-Makassar juga berperan penting dalam membawa proses implementasi dan nilai-nilai Sulapa Eppa budaya Bugis secara bersama-sama. Pada Badan Amil Zakat Nasional Kabupaten Sidrap, laporan keuangan (financial statement) yang akuntabel dan transparan dibuat dengan presentasi berdasarkan nilai Matanre Siri, seperti lempu' (jujur). Sehingga Metanre Siri dikonstruksi dengan maksud untuk mencapai keseragaman atau keseragaman yang telah ditetapkan oleh penguasa.